The Construction of Identity of “Sultan” and Hedonism on TikTok @indrakenz - Diyah Ayu Karunianingsih (Jurnal Ilmu Komunikasi, 2022)
The number of TikTok users has increased significantly. The phenomenon of influencers and TikTok stars competing to present content to go viral and appear on the For Your Page (FYP). One of them is the content of luxury life, hedonism, and showing off branded goods. TikTok has become an arena for spectacle and construction of "sultan" identity and hedonism. Indra Kesuma is an Indonesian TikTok star and influencer who is viral among teenagers by presenting luxurious and hedonistic life and showing off branded goods, with the famous words “murah banget”. This is the background for the author to analyze TikTok as a spectacles media and the construction of the identity of “sultan” and hedonism on TikTok @indrakenz. The qualitative descriptive method with an analytical model, namely analyzing the words in the caption, the hashtags, the words spoken by Indra Kesuma, and the activities shown in the video with the theory construction of identity, hedonism, and spectacle. The results show that the construction of the identity of “sultan” and hedonism is carried out by writing the caption “sultan”, hashtag #sultan, the word “sultan” spoken by Indra Kesuma, as well as activities of the sultan such as buying luxurious cars, having luxurious dishes, and wearing fancy apparels. TikTok has become a media of spectacle for the spread of ideology about role models and standards of living for teenagers, namely the hedonistic life of the sultan. The research contribution provides knowledge that TikTok as a medium for teenagers to construct the identity of “sultan”, as well as being the spectacle of spreading ideology about the role model of the sultan.